Guinea Pig as a Model of Infectious Diseases - Padilla-Carlin, Danielle J; McMurray, David N; Hickey, Anthony J (Comparative medicine, 2008)
The words 'guinea pig' are synonymous with scientific experimentation, but much less is known about this species than many other laboratory animals. This animal model has been used for approximately 200 y and was the first to be used in the study of infectious diseases such as tuberculosis and diphtheria. Today the guinea pig is used as a model for a number of infectious bacterial diseases, including pulmonary, sexually transmitted, ocular and aural, gastrointestinal, and other infections that threaten the lives of humans. Most studies on the immune response to these diseases, with potential therapies and vaccines, have been conducted in animal models (for example, mouse) that may have less similarity to humans because of the large number of immunologic reagents available for these other species. This review presents some of the diseases for which the guinea pig is regarded as the premier model to study infections because of its similarity to humans with regard to symptoms and immune response. Furthermore, for diseases in which guinea pigs share parallel pathogenesis of disease with humans, they are potentially the best animal model for designing treatments and vaccines. Future studies of immune regulation of these diseases, novel therapies, and preventative measures require the development of new immunologic reagents designed specifically for the guinea pig.